ChemInform Abstract: An Examination of the Palladium/Mor‐DalPhos Catalyst System in the Context of Selective Ammonia Monoarylation at Room Temperature. Issue 25 (3rd June 2013) - Alsabeh, Pamela G.; Lundgren, Rylan J.; McDonald, Robert; Johannsson Seechurn, Carin C. C.; Colacot, Thomas J.; Stradiotto, Mark
Abstract A wide range of aryl‐ and heteroaryl‐chlorides and tosylates are converted to the corresponding amines.